Efektivitas Kortikosteroid Intranasal vs Antihistamin Oral pada Rhinitis - Dwiyanti, Fitri; Ferdiani, Fivien; Imanto, Mukhlis (CV. Jasa Sukses Abadi, 2026)
Allergic Rhinitis (AR) is a chronic inflammatory disorder of the nasal mucosa mediated by immunoglobulin E after exposure to specific allergens. It is characterized by rhinorrhea, nasal obstruction, sneezing, and nasal itching. AR has a high and increasing global prevalence and significantly affects quality of life, sleep quality, cognitive performance, and daily productivity. Effective management is required to control symptoms and prevent complications and comorbidities. This literature review compares the effectiveness of intranasal corticosteroids (INCS) and oral antihistamines (OAH) in the management of allergic rhinitis. A literature search was conducted using the Google Scholar database for studies published between 2017 and 2025, using the keywords “allergic rhinitis”, “allergic rhinitis therapy”, and “intranasal corticosteroids and oral antihistamines”. Included articles were accessible, written in English or Indonesian, and discussed the comparative effectiveness of INCS and OAH. Studies published before 2017 were excluded. The findings show that oral antihistamines effectively relieve early-phase, histamine-mediated symptoms such as sneezing, nasal itching, and rhinorrhea, with a rapid onset of action suitable for intermittent use. In contrast, intranasal corticosteroids are more effective in reducing nasal congestion and controlling persistent inflammation due to their broad anti-inflammatory effects. INCS also improve ocular symptoms and provide greater overall improvement in health-related quality of life compared to antihistamines alone. Overall, intranasal corticosteroids are recommended as first-line therapy for moderate to severe or persistent allergic rhinitis, while oral antihistamines remain useful for mild symptoms or as adjunctive therapy according to individual clinical needs.